(untitled) (Journal of Organizational Psychology, 2020)
The integrity of performance appraisal systems depends on the appraiser, responsible for providing employees with objective evaluations. Research has shown that managers often feel anxiety when conducting employee appraisals and consequently may withhold negative feedback, compromising the appraisal process. We examined, using Grounded theory, the manager’s experience of performance appraisal anxiety with 13 experienced managers. We found that a primary cause of PA anxiety was the fear that the employee would react negatively to the feedback. Further, our participants described productive levers they use to reduce PA anxiety while preserving the integrity of the feedback provided. PA anxiety was reduced by implementing more frequent feedback, training to increase manager confidence in delivering feedback effectively, and adoption of an employee-centered approach to PA.